Byzantine Military Pragmatism vs. Imperial Prejudice: Possible Reasons for Omitting the Armenians from the List of Hostiles in Maurice’s “Strategikon” - Ayvazyan, Armen (Armenian Folia Anglistika, 2011)
Strategikon which is ascribed to Maurice Emperor (582‒602) was an important strategic and tactical manual designed for the Byzantine Military. The work contains a special chapter which, as the author claims, analyses the tactics and features of the peoples who are able to harm the Byzantine Empire. Persians, Scythians, i.e. Avars, Turks and other fair-haired peoples, including Franks, Lombards and Slavic nations are mentioned in the chapter. Each of the ethnically different nations is given an objective and sometimes a rather high evaluation of their military abilities and features on the one hand and in proportion to its empirical prejudice, on the other hand. Surprisingly, Armenians, who had fought against the Byzantine troops on numerous occasions both independently and more often as an ally of Iran or its subordinate forces, were not included in the list of the enemy nations or potential opponent nations in Strategikon. The present article examines the Armenian–Byzantine relations in the time period and suggests possible reasons for removing Armenians from the list of the potential enemies.